PENGARUH JUMLAH KRIB TIPE ZIGZAG TERHADAP KECEPATAN ALIRAN PADA SUNGAI KRUENG ACEH - Suryati Suryati; Eldina Fatimah; Masimin Masimin (Prodi Magister Teknik Sipil Unsyiah, 2020)
The velocity at the inner turns of the Krueng Aceh river which is ± 100 meters from the Pango Bridge results in the collapse of river banks and endangers public facilities. For this reason, it is necessary to design a construction to protect the river bank. One of the alternatives is to use groyne construction. This study simulated the gropozag type groyne as an alternative form of groyne to be installed in the field. The aim of the study is to see the effect of gropozag type groyne on the river speed using the Surfacewater Modeling System (SMS) program to predict the direction of flow after the installation of the crib. Calibration is performed by determining the relative error value using velocity measurement data. This study uses gropozag groyne type with a length of 2,47 m (6 % B), 3 perpendicular groyne formation placements with an inclination of 10o,20o and 30o towards the upstream and the downstream area in 2 variations, namely 5-unit groynes and 3-unit groynes. The results shows that the RMA2 model obtained results that are close to the measurement value, where the value of the relative error obtained is 7.74% in cross 1 and 6.27% in cross 2. The lengthwise analysis of maximum velocity of 5-unit groynes shows that the maximum velocity occurs at V3 of 4,029 m/sec in the KRA5 formation (10o inclined to downstream of 5 units). Maximum speed of 3-unit groynes at V3 with KTA3 formation (3 perpendicular units) is 3,612 m/s. The number of groynes installed also affects the velocity of the simulation results. The velocity of the 5-unit groynes series is greater than that of the 3-unit groynes series.